Playing Lotteries and Betting on Sporting Events A Behavioral Economics Perspective - Mikulka, Jakub; Koblovský, Petr; Koten, Silvester van, 1970-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This thesis deals with the relationship between mood and behavior of bettors using a dataset provided by a betting company, Chance a.s., which operates in the Czech Republic. We consider three types of proxies for the mood: weather in regions, sport successes and the results of elections, and we build a fixed effect model to estimate the effect of mood on betting behavior. We provide strong evidence that the weather proxy has a significant effect on daily turnovers of the betting company and there also seems to be an effect of sport optimism. On the contrary, we failed to find any impact of elections. The results show that better mood tend to discourage clients from sports and lottery betting which is consistent with the increase in risk aversion or the depletion of a common self-control resource due to active mood regulation attempts. Additionally, we provide an evidence that the intra-month cycle in turnovers corresponds to liquidity constraint of bettors which disproves the permanent income hypothesis.
Vedoucí práce: Petr Koblovský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: politologie [obor dipl. práce]; diplomové práce; master's theses